Physicochemical Analysis and Biodiesel Potential of Bottle Gourd (Lagenaria Siceraria) Seed Oils - Rufai Usman Fakai (MultiTech Publisher, 2023)
Lagenaria siceraria commonly known as bottle gourd or calabash, is a versatile plant species that has been widely cultivated for its edible fruit and various other uses. In this study, the physicochemical properties of Lagenaria siceraria oil were investigated to evaluate its potential and industrial applications. The oil was extracted from the seeds of Lagenaria siceraria using a soxhlet extraction method, and its physicochemical parameters, including percentage yield, acid value, peroxide value, saponification value, iodine value, and fatty acid composition, were determined. The results revealed that Lagenaria siceraria oil had a low moisture content, indicating its good storage stability. The acid value and peroxide value were found to be within acceptable limits, suggesting that the oil had low levels of free fatty acids and oxidative rancidity. The saponification value indicated the average molecular weight of the oil, while the iodine value reflected its unsaturation degree. These parameters are crucial for determining the oil's suitability for various industrial applications. Furthermore, gas chromatography-mass spectrometry (GC-MS) analysis of the fatty acid composition demonstrated that Lagenaria siceraria oil primarily consisted of unsaturated fatty acids, with linoleic acid (C18:2) and oleic acid (C18:1) being the major components. The presence of these essential fatty acids suggests that Lagenaria siceraria oil can be used for biodiesel production.